Social Networks, Pandemic and Higher Education in the Visual Arts: Student Perception - Pillacela-Chin, Luisa Alejandrina; López-San Segundo, María del Carmen (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
With the aim of finding out which social networks were most used by students in the field of university education in the visual arts during the Covid-19 pandemic, a case study of the Visual Arts degree course at the University of Cuenca was undertaken. The methodology was based on structured interviews with students who studied during the most critical periods: the confinement and the new normality. The interviews were conducted between December 2022 and February 2023. The results help to assess particularities whose understanding is useful for the planning of new training strategies.